2020
DOI: 10.3390/cells9081815
|View full text |Cite
|
Sign up to set email alerts
|

The Secret Garden of Neuronal circRNAs

Abstract: High-throughput transcriptomic profiling approaches have revealed that circular RNAs (circRNAs) are important transcriptional gene products, identified across a broad range of organisms throughout the eukaryotic tree of life. In the nervous system, they are particularly abundant, developmentally regulated, region-specific, and enriched in genes for neuronal proteins and synaptic factors. These features suggested that circRNAs are key components of an important layer of neuronal gene expression regulation, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 157 publications
(305 reference statements)
0
14
0
Order By: Relevance
“…FEZ1 binds with DISC1 and increases neurite outgrowth in response to NGF (42). Qki can bind with intronic regions and participate in the biogenesis of circRNAs (43). Abnormal expression of Qki might be associated with the observed dysregulation of cricRNAs in schizophrenia (44).…”
Section: Diagnostic Value Of Mirnas In Schizophreniamentioning
confidence: 99%
“…FEZ1 binds with DISC1 and increases neurite outgrowth in response to NGF (42). Qki can bind with intronic regions and participate in the biogenesis of circRNAs (43). Abnormal expression of Qki might be associated with the observed dysregulation of cricRNAs in schizophrenia (44).…”
Section: Diagnostic Value Of Mirnas In Schizophreniamentioning
confidence: 99%
“…For instance, it remains unclear whether circRNAs act on microRNAs simply by blocking their function and/or by affecting their stability. In this sense, although it has been speculated that circRNAs might trigger TDMD like linear RNAs, this premise was never formally and experimentally tested so far (Gasparini et al , 2020). Our data suggest the opposite: even when expressed at comparable levels, artificial circular RNAs of identical sequence to those of TDMD-inducing linear RNAs, prove incapable of inducing TDMD (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…A study in humans comparing the brains of individuals with ASD and controls showed novel circRNAs from the RIMS2 gene, which encodes a presynaptic terminal protein related to vesicular exocytosis [ 94 ]. An ASD mouse model showed different levels of circRNAs in hippocampus [ 95 ]; notably, circRNAs were highly localized in synaptic region [ 94 ]. These results support further investigations into the mechanisms of non-coding RNAs involvement in ASD pathophysiology.…”
Section: Local Translation and Asdmentioning
confidence: 99%